2010
DOI: 10.1186/1756-3305-3-32
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected canine vector-borne diseases between urban animal shelter and rural hunting dogs in Korea

Abstract: A serological survey for Dirofilaria immitis, Anaplasma phagocytophilum, Ehrlichia canis, and Borrelia burgdorferi infections in rural hunting and urban shelter dogs mainly from southwestern regions of the Republic of Korea (South Korea) was conducted. From a total of 229 wild boar or pheasant hunting dogs, the number of serologically positive dogs for any of the four pathogens was 93 (40.6%). The highest prevalence observed was D. immitis (22.3%), followed by A. phagocytophilum (18.8%), E. canis (6.1%) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
7
27
1
Order By: Relevance
“…The seroprevalence was higher in dogs living in the Plain zone and in rural areas than it was in the Foothill zone and in urban areas, which was also reported by Lim et al (2010) in Korea and Costa et al (2007) in Brazil. This may be explained by a number of factors, such as suitable environmental conditions for tick survival (for example, warmer temperatures that lead to higher tick infestation rates) and the lack of ectoparasite control programs in rural areas and in the Plain zone.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The seroprevalence was higher in dogs living in the Plain zone and in rural areas than it was in the Foothill zone and in urban areas, which was also reported by Lim et al (2010) in Korea and Costa et al (2007) in Brazil. This may be explained by a number of factors, such as suitable environmental conditions for tick survival (for example, warmer temperatures that lead to higher tick infestation rates) and the lack of ectoparasite control programs in rural areas and in the Plain zone.…”
Section: Discussionsupporting
confidence: 68%
“…Apart from climatic conditions, certain epidemiological factors such as vector distribution, animal behavior, age of the population studied (RODRIGUEZ-VIVAS et al, 2005;TRAPP et al, 2006;LIM et al, 2010), management practices and habitat where the animals live (SAINZ et al, 1995) may affect the prevalence of canine ehrlichiosis. The prevalence of E. canis in dogs that lived in rural areas was 21% in this study, which was much higher than …”
Section: Discussionmentioning
confidence: 99%
“…Lower percentages (2.72-5.5%) were reported from France (Pantchev et al 2009), Romania (Mircean et al 2012), and Spain (Miró et al 2013). In other countries, such as Germany (Kohn et al 2011), the United States (Beall et al 2008), and Korea (Lim et al 2010), much higher seropositivity (18.8-43.2%) was found amongst the local dogs. The seroprevalence of this rickettsial infection in dogs has a very wide range worldwide, even between the different regions of a country (Kohn et al 2011, Miró et al 2013.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies found older dogs having an increased risk of D. immitis infection that was thought to be due to the prepatency period of the parasite (Song et al, 2003;Tudor et al, 2009;Lim et al, 2010;Vieira et al, 2014). According to the literature (Montoya et al, 1998;Yildirim et al, 2007) another important risk factor is the time of exposure to the vector; in fact these dogs were kept in outdoor shelters, where they were more likely to acquire this infection.…”
Section: Discussionmentioning
confidence: 99%